Strategies for Improving the Creative Work Environment through Managing the Physical and Psychological Environments of Employees: Literature Study - Fajar Wirahadi Kuncoro; Helmi Buyung Aulia Safrizal (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to investigate how to improve a creative work environment through physical and psychological management of employees. This study uses literature studies by collecting data from various sources such as academic journals, books, and related articles. Data were analyzed descriptively qualitatively by comparing and evaluating the strategies used in previous studies. The research findings show that managing the physical and psychological environment of employees can increase creativity and productivity in the workplace. Some effective strategies include creating an environment that supports collaboration and social interaction, providing creative space and facilities that allow out-of-the-box thinking, and providing psychological support to deal with stress and burnout. This research provides valuable insights for companies and managers in improving the work environment and increasing employee creativity